LMX ( Leader Member Exchange ) dan Karakteristik Pekerjaan Terhadap Career Plateau Dengan Mediasi Kepuasan Kerja - Diah Ariefiana; Euis Soliha (Journal of Economics and Business, 2021)
This study aims to determine the effect of LMX (leader member exchange) and job characteristics on the carrier plateau by mediating job satisfaction. Data collection methods used are questionnaires, editing, coding, scoring and tabulation. Analysis of the data used in this study is the analysis of respondents' descriptions, variable description analysis, Validity Test, Reliability Test ,Regression Test, and Sobel Test. The population in this study were 143 employees who worked at Muhammadiyah General Hospital Darul Istiqomah Kendal while the sampling technique in this study used a census, where all employees became respondents. The results of the study show that Leader member exchange (LMX) has a positive and significant effect on job satisfaction. Job characteristics have a positive and significant effect on job satisfaction. Leader member exchange (LMX) does not affect career plateau. Job characteristics have a negative and significant effect on career plateau. , Job satisfaction has a negative and significant effect on career plateau, job satisfaction mediates perfectly the influence of leader member exchange (LMX) on career plateau. Job satisfaction mediates the effect of job characteristics on career plateau on employees of Darul Istiqomah Kendal Hospital.